EFEITO NEFROPROTETOR DA AÇÃO DE PROBIÓTICOS EM RATOS INTOXICADOS POR DICROMATO DE POTÁSSIO - Parra, Matheus Campos Garcia (2015)
The objective was to evaluate the effect of probiotic on renal function in intoxicated Wistar rats by potassium dichromate (K2Cr2O7). We used 80 male Wistar rats, that were 21 to 25 days old, randomly divided into two treatments (n = 40 rats/treatment). In the DK treatment the animals consumed 0, 12, 24 and 36 mg of K2Cr2O7 added to the diet and in the DK+P treatment the rats consumed 0, 12, 24 and 36 mg of K2Cr2O7 in the diet with 0.2% probiotic. Those animals consumed their respective diets for 90 days, then, they were euthanized by exsanguination and blood samples were taken to evaluate serum creatinine and urea levels and histopathological analysis of the kidneys were realized. Serum creatinine levels in the DK+P treatment was significantly (p<0.05) lower in relation to the DK treatment in all dichromate doses analyzed. Serum urea levels did not differ significantly (p>0.05) between the DK and DK+P treatments. There was no significant difference (p>0.05) in serum creatinine and urea concentrations in the rats that consumed 0 and 12 mg of dichromate and probiotic, but in the other animals serum creatinine and urea increased significantly (p<0.05) along with increasing doses of the dichromate in both experimental treatments. The rats in DK and DK+P treatments showed hydropic degeneration in renal tubules at all doses of K2Cr2O7. The DK treatment rats showed interstitial nephritis. It was concluded that supplementation with the probiotic was beneficial for glomerular filtration in rats intoxicated with low doses of potassium dichromate, but did not prevent the tubular hydropic degeneration in Wistar rats intoxicated by potassium dichromate.